Increased dairy farm methane concentrations linked to anaerobic digester in a five‐year study. Issue 2 (9th March 2020) - Debruyn, Zachary; VanderZaag, Andrew; Wagner‐Riddle, Claudia
Abstract: Organic waste materials are sources of anthropogenic methane (CH4 ) emissions. Anaerobic digestion (AD) is a technology that produces biogas from organic waste materials, and CH4 is the primary component of biogas. Unintended emission of CH4 from biogas facilities could undercut the environmental benefits of this technology. The objective of this study was to determine if the implementation of an AD system affected ambient CH4 concentrations ([CH4 ]) on a commercial dairy farm over 5 yr, from before installation into full operation. Concentrations at 4.5‐m height on a tower receiving wind that originated from various directions, comprising components of the dairy farm such as the AD facility, crop fields, or main barn, were measured using a closed‐path tunable diode laser trace‐gas analyzer. In 2012 and 2013, the first 2 yr of AD operation, [CH4 ] was not significantly different than pre‐AD levels in 2011 (2.04 ± 0.01 μl L −1 ). However, mean [CH4 ] increased to 2.47 ± 0.03 and 2.48 ± 0.04 μl L −1 in 2014 and 2015, respectively, and the occurrence of high [CH4 ] (>10 μl L −1 ) increased from <0.05% in Year 1 (pre‐AD) to 12% in Years 4 and 5. These elevated concentrations were related to an increased use of food waste feedstocks over time and suggest that the biogas system was a source of fugitive CH4 emissions. Food waste materials have a high biogas potential and are a valuable resource that require appropriate facility design and management to fully harness their benefits.